intellectual quotient, spiritual THE EFFECT OF INTELLECTUAL QUOTIENT, SPIRITUAL QUOTIENT, INDIVIDUAL CHARACTERISTICS AND ACHIEVEMENT MOTIVATION TOWARD COMPETENCE, ORGANIZATIONAL COMMITMENTS AND LECTURERS’ DEVELOPMENT (STUDY AT ISLAMIC UNIVERSITIES IN EAST JAVA): Human Resource Management - Nur Irawan, Rizal (Archives of Business Research, 2019)
The purpose of this study was to analyze the variables of intellectual quotient, spiritual quotient, individual characteristics and achievement motivation on competence, organizational commitment and career development of lecturers at Islamic Universities in East Java. This research approach employed a population of permanent lecturers who are appointed by foundations or managers and hold functional positions of at least expert assistants at the Islamic University in East Java based on the principle of ahlussunnahwaljamaahannadliyahby taking 162 respondents as samples. Meanwhile, the technique of analysis used Structural Equation Model (SEM). The results of the analysis showed that intellectual quotient, spiritual quotient, individual characteristics and achievement motivation influence competence and commitment while only intellectual quotient, individual commitment and individual characteristics affect the career development of lecturers. Yet, motivation has no influence on organizational commitment.